Jonah - Walton, John H. 1952- (Grand Rapids, MI Zondervan, 1982)
Includes bibliographical references.
Published in 1988 in a compilation with Obadiah / by Bryan E. Beyer, which see also.
Keywords: Bible. O.T. Jonah -- commentaries